Challenges in Pathologic Staging of Renal Cell Carcinoma: A Study of Interobserver Variability Among Urologic Pathologists. (September 2018) - Williamson, Sean R.; Rao, Priya; Hes, Ondrej; Epstein, Jonathan I.; Smith, Steven C.; Picken, Maria M.; Zhou, Ming; Tretiakova, Maria S.; Tickoo, Satish K.; Chen, Ying-Bei; Reuter, Victor E.; Fleming, Stewart; et al.
Abstract : Staging criteria for renal cell carcinoma differ from many other cancers, in that renal tumors are often spherical with subtle, finger-like extensions into veins, renal sinus, or perinephric tissue. We sought to study interobserver agreement in pathologic stage categories for challenging cases. An online survey was circulated to urologic pathologists interested in kidney tumors, yielding 89% response (31/35). Most questions included 1 to 4 images, focusing on: vascular and renal sinus invasion (n=24), perinephric invasion (n=9), and gross pathology/specimen handling (n=17). Responses were collapsed for analysis into positive and negative/equivocal for upstaging. Consensus was regarded as an agreement of 67% (2/3) of participants, which was reached in 20/33 (61%) evaluable scenarios regarding renal sinus, perinephric, or vein invasion, of which 13/33 (39%) had ≥80% consensus. Lack of agreement was especially encountered regarding small tumor protrusions into a possible vascular lumen, close to the tumor leading edge. For gross photographs, most were interpreted as suspicious but requiring histologic confirmation. Most participants (61%) rarely used special stains to evaluate vascular invasion, usually endothelial markers (81%). Most agreed that a spherical mass bulging well beyond the kidney parenchyma into the renal sinus (71%) or perinephric fat (90%) did not necessarily indicate invasion. Interobserver agreement in pathologic staging of renal cancer is relatively good among urologic pathologists interested in kidney tumors, even when selecting cases that test the earliest and borderline thresholds for extrarenal extension. Disagreements remain, however, particularly for tumors with small, finger-like protrusions, closely juxtaposed to the main mass. Abstract : Supplemental Digital Content is available in the text.